Managing emerging challenges of Coronavirus disease 2019 (COVID-19) in dentistry - Nazmiye Şen; Ryan Olley; Ayşem Günay; Gülsüm Ak (Istanbul University, 2020)
Dental centers have been referred to as a hub or reservoir for infection, where healthcare professionals and other staff, patients and the public together may potentially spread pathogenic microorganisms. This may occur via saliva, skin or indirectly through air, water, and contaminated surfaces or instruments. Everyone should therefore be considered as potential sources of infection. During a pandemic, limiting unnecessary care has been adopted as a clinical measure for some patient's, to reduce the risk of cross-infection in the short term. However, in order to enable continuation of necessary and qualified care, dental processes need to follow specific infection control strategies in order to prevent transmission of emerging pandemic risks following COVID-19. In this article, we develop a tool with practical recommendations to mitigate infection risks before, during and following pandemics to enable ongoing dental care provision in primary and secondary care based on national and global recommendations.